Pengaruh pH dan Lama Fermentasi terhadap Karakteristik pada Nata de Papaya - Marisal Haq; Ulfa Maulida Farid; Ahmad Mundzir Romdhani; Mohammad Nurul Hidayatullah (Program Studi Teknologi Hasil Pertanian, 2025)
The utilization of papaya in Indonesia, particularly in Sumenep Regency, remains suboptimal as most harvests are left to ripen on the tree without further processing. However, papaya contains high nutritional value and organic materials that can be processed into fermented products, such as nata. Nata is an extracellular polysaccharide produced by the bacterium Acetobacter xylinum in media rich in sugar and acid. This study aims to determine the effect of pH and fermentation duration on the physical characteristics of nata de papaya, including thickness, color, texture, and aroma. The research method employed a Completely Randomized Design (CRD) with variations in fermentation duration (4, 7, and 10 days) and acidity levels (pH 4 and 5). To test the influence of these variables, data were analyzed using a One-Sample t-test with a significance level of 0.005. The results showed that nata de papaya fermented for 10 days at pH 4 produced a thickness of 6.17 mm. A dominant white color was observed in the 7-day fermentation at pH 4, while a chewy texture and fresh acidic aroma emerged in the 7 and 10-day fermentations; meanwhile, the 4-day fermentation resulted in a neutral aroma. Statistical analysis proves that pH and fermentation duration have a significant effect on all physical characteristics of Nata de Papaya.